CUTANEOUS VASCULITIS IN PATIENTS WITH RHEUMATOID ARTHRITIS - David Vladimirovi Bestaev; D E Karateev (Научно-практическая ревматология, 2014)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammatory and destructive joint damage and extra-articular manifestations involving various organs and systems in the pathological process. One of systemic manifestations of RA is cutaneous rheumatoid vasculitis (RV). Factors predisposing to the development of RV in RA patients include male gender, high titers of rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP) antibodies, antineutrophil cytoplasmic antibodies, and presence of other extra-articular manifestations. RV may develop due to immune complex deposition on the vascular walls. RV activity correlates with high level of RF, anti-CCP and anti-nuclear antibodies. The typical signs of RV include peripheral gangrene, mononeuritis multiplex, as well as scleritis, pericarditis and lung damage. However, skin lesions, such as periungual infarction (digital arteritis), capillaritis, livedo reticularis, and chronic leg ulcers, are more common signs. Development of RV worsens the prognosis of the disease. The 5-year survival rate of RV patients was 28–40% until the principle of early administration of basic anti-inflammatory drugs was implemented. RV is not an independent disease; in most cases, RV alone does not impose a threat to a patient and requires no treatment. Special treatment of cutaneous vasculitis is required in case of venous ulcers only. The article discusses the pathogenesis issues and strategies of RV treatment in RA patients.